2008
DOI: 10.1091/mbc.e07-07-0717
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Carboxyl-Terminal Domain of the Proteasomal Subunit Rpn11 in Maintenance of Mitochondrial Structure and Function

Abstract: We have previously demonstrated that the C-terminal part of Rpn11, a deubiquitinating enzyme in the lid of the proteasome, is essential for maintaining a correct cell cycle and normal mitochondrial morphology and function. The two roles are apparently unlinked as the mitochondrial role is mapped to the Carboxy-terminus, whereas the catalytic deubiquitinating activity is found within the N-terminal region. The mitochondrial defects are observed in rpn11-m1 (originally termed mpr1-1), a mutation that generates R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 43 publications
6
69
0
Order By: Relevance
“…Expression of the carboxyl terminus of Rpn11 (GST-C Rpn11 ) 2 partially suppressed the diverse defects of rpn11-1, consistent with other studies that showed the this domain is required for Rpn11 function (21)(22)(23). We found that the high levels of multiubiquitinated proteins in rpn11-1 were bound to shuttle factors.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Expression of the carboxyl terminus of Rpn11 (GST-C Rpn11 ) 2 partially suppressed the diverse defects of rpn11-1, consistent with other studies that showed the this domain is required for Rpn11 function (21)(22)(23). We found that the high levels of multiubiquitinated proteins in rpn11-1 were bound to shuttle factors.…”
supporting
confidence: 89%
“…Direct binding studies failed to reveal any interaction between FLAG-rpn11-1 and GST-C Rpn11 , indicating that suppression is not achieved by dimerization of these protein sequences (data not shown and Ref. 22). Because rpn11-1 protein is catalytically active but destabilizes proteasomes, we propose that the carboxyl terminus promotes proteasome stability, consistent with previous reports showing its requirement for Rpn11 function (21)(22)(23).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is derived from pYEF1mtRFP, 44 which was constructed using PYX-mtGFP. 45 The selectable marker was changed from URA3 (pYEF1mtRFP) to LEU2 (pYEF2mtRFP).…”
Section: Discussionmentioning
confidence: 99%